Ответы и объяснения

Лучший Ответ!
  • WinDe
  • середнячок
2014-03-19T19:33:38+00:00
 1)  P2(+3)O3(-2)  + Fe(+2) (N(+5)O3(-2))2 --> P2(+5)O5(-2) + Fe(+2)O(-2) + N(+4)O2(-2)
   
2P(+3) - 4e -->2P(+5)   /4/  1
2N(+5) + 2e--> 2N(+4)  /4/  2
   1P2O3 + 2Fe(NO3)2 --> 1P2O5 + 2FeO + 4NO2


 2)   P2(+3)O3(-2) + Ar(+1)N(+5)O3(-2) --> P2(+5)O5(-2) + N(+4)O2(-2) + Ar(0)
  2P(+3) -4e --> 2P(+5)  / 4/  1
 
Ar(+1) + 1e -- > Ar(0)  /   /  2
                                / 2 /
N(+5) + 1e --> N(+4)  /    /   2
  1P2O3 + 2ArNO3 --> 1P2O5 + 2NO2 + 2Ar